Health data privacy and confidentiality rights: crisis or redemption? - Faria, Paula Lobato de (2017)
A B S T R A C T - Although widely analyzed by authors and theoretically valued by the public, the right tohealth data confidentiality seems to be more of an academic figure than a real protectedright. This happens due to intrinsic problems with the practical enforcement of somepatient’s rights, but is getting more notorious in contemporary society.This article describes the rights to health data privacy and confidentiality in their classicalcontours, focusing on areas of consensus and controversy and analyzing the recent trans-formations in society that are causing a crisis in these same rights. We agree that there arereasons to believe that there are no novel legal instruments in Health Law to redeem theserights, except for European Data Protection Law. Here, we briefly analyze the new Europeandata protection draft regulation, which intends to bring reinforced tools on this domain.We conclude that the juridical aura that still embraces the right to medical and geneticdata confidentiality in Health Law and Bioethics seems to no longer have a practical sense.However, despite this perception, the essential dimension of individual freedom relating topersonal information and to the notion that the less is known about us the freer we all are isstill very relevant and so Health Law needs to dedicate more attention to the transformationsof privacy and confidentiality in the medical and genetic fields in order to maintain themprotected and respected.